Write great code. - Hyde, Randall (No Starch Press, 2006)
Today's computer science students aren't always taught how to choose high-level language statements carefully to produce efficient code. Write Great Code, Volume 2: Thinking Low-Level, Writing High-Level shows software engineers what too many college and university courses don't: how compilers translate high-level language statements and data structures into machine code. Armed with this knowledge, readers will be better informed about choosing the high-level structures that will help the compiler produce superior machine code, all without having to give up the productivity and portability ben.